The Economic-Financial Viability of Using Eco-Friendly Cups as a Substitute for Diposable Cups at the State Univesity of Northern Paraná - Paulo Rogério Alves Brene; Bruna da Conceição Costa Silva; Flávia Debiagi; Maria Luiza Motta D’Avila Oliveira (Journal of Sustainability Perspectives, 2023)
The present work aims to calculate the economic-financial viability of using eco-friendly cups as a substitute for disposable cups, based on data from the State University of Northern Paraná. In Brazil, their recycling is not attractive from a commercial standpoint, and their inadequate disposal contaminates soils and watercourses. Nevertheless, regarding the institution, there is a high consumption of these materials in the exercise of activities and in environments serving external audiences. In this context, the replacement of disposable cups with reusable containers in the higher education institution (HEI) is an alternative to assist both sustainability and economy. The evaluation for the possible substitution consisted of an economic-financial analysis (Net Present Value - NPV) from several scenarios. As a conclusion, it can be said that this study presents an economic and sustainable alternative to the use of disposable cups within a HEI.